Participatory strategies for implementing sustainable agrifood systems in the Amazon - Maya, Diana; Guaqiuetá, Victoria; Correal, Antonia; Rodríguez, Luz A. (2024)
This Experience Exchange and Learning Route was proposed within the CGIAR initiative Low Emission Food Systems (Mitigate+) as a process to strengthen local capacities, based on the needs identified in the characterization of production systems carried out through participatory workshops in Belén de los Andaquíes and La Montañita Caquetá during 2023. The objective of the exchange of experiences was to strengthen the organizational and management capacities of producers and producers' organizations in the territory by providing knowledge and tools to enable the implementation of strategies for mitigation and adaptation to climate change. We address the following topics: climate change adaptation and mitigation, participatory innovation, low-emission food systems, project formulation and business plans. Including a gender perspective and permanent reflections on the aspects related to equity were fundamental in the development of the training activities and the exchange of experiences.